Role of moveable guide vane with various configurations in controlling the vortex-induced vibration of twin-box girder suspension bridges: An experimental investigation. (15th April 2023) - Zhou, Rui; Lu, Peng; Gao, Xiaodong; Ge, Yaojun; Yang, Yongxin; Zhang, Lihai
Highlights: VIV tests were conducted to study the VIV control effects of a moveable guide vane with various horizonal length and stiffness. The moveable guide vane significantly reduce the VIV of the bridge with an immovable guide vane or without a guide vane. The increase of the horizontal length and stiffness have a negative impact on VIV control of the twin-box girder suspension bridge. The leeward guide vane could play an important role in the VIV suppression when the total stiffness is larger than 19 g/mm. Abstract: The purpose of this paper is to investigate the effects of a moveable guide vane with various configurations ( i.e., horizonal length and stiffness) in controlling the vortex-induced vibration (VIV) of a long-span suspension bridge with twin-box girder. First, a series of VIV tests of the 1:50 scaled ratio of sectional model with various guide vane configurations were performed. The vertical and torsional displacements of the twin-box girder as well as the vertical response of the windward and leeward guide vane measured to analyze the movement characteristics of the main girder and guide vanes, respectively. The test results show that, the moveable guide vane could significantly reduce the maximum vertical and torsional displacement responses of the main girder with an immovable guide vane or without a guide vane, especial under the most unfavorable wind attack angle of +3°. In addition, a moveable guide vane with relatively low stiffness could produce a better outcome of VIV control. Furthermore, the increase of the horizontal length of the guide vane could have a negative impact on the VIV control of the bridge. Importantly, the maximum vertical amplitude of the moveable guide vane is generally larger than that of the main girder, indicates that the leeward guide vane could play an important role in the VIV suppression when the stiffness of the guide vane is over certain threshold ( e.g., 19 g/mm).